Association of canine juvenile generalized demodicosis with the dog leukocyte antigen system - It, Veronica (2010)
Demodectic mange is a well-known parasitic skin disease characterized by the presence of a larger than normal number of Demodex mites (Demodex canis) in the skin of dogs. Recent research has suggested that major histocompatibility complex (MHC) class II expression is higher in the skin of dogs suffering from demodicosis than in normal ones. We have investigated whether canine Dog Leukocyte Antigen (DLA) class II alleles are associated with canine juvenile generalized demodicosis (JGD). In the present study, the analysis of microsatellite markers (FH2202, FH2975 and FH2054) linked to DLA was made in Boxer, Argentinean Mastiff and mixed breed dogs. DNA samples from 56 dogs affected with the disease and 60 breed-matched controls collected in Argentina were analysed. A highly significant association, in some of the analysed markers, in all breeds with the presence of demodicosis was observed with P < 0.05 and odds ratio (OR) ≥5. The results of this study suggest that an underlying DLA association exists with demodicosis in dogs and that this may represent an important immunological risk factor in the aetiology of this condition. This information could be used in the future to develop diagnostic tests to prevent canine JGD.